Mediating Impact of Psychological Autonomy on the relationship between Entrepreneurship Engagement and Wellbeing - Asriyal; Amrizal; Koesmawan; Mulyati, Henny; Husnayeti (International Journal of Psychosocial Rehabilitation, 2020)
Present study aims to investigate the mediating role of psychological autonomy (PSA) on the relationship between entrepreneurship engagement (EENG) and well-being (WB). For this purpose, data are collected through an online questionnaire survey from 267 entrepreneurs and business owners of different industries. The study analyzed the data by using smart PLS’s SEM. Smart PLS used variances-based approach of partial least square that explains measurement errors and therefore accounts for providing more precise results as compare to OLS regressions. The results show significant and positive relationship between EENG and WB. PSA mediates the linkage between EENG and WB. The study suggested that EENG should be promoted as it helps individuals in establishing their own goals, increases the level of competency and enhances WB.